2017
DOI: 10.1080/0267257x.2017.1373693
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory consumption and consumer compromises: a state-of-the-art review

Abstract: Compensatory consumption has been an increasingly researched yet widely debated area of consumer behaviour over the last 20 years. Extant research formulates the term as overwhelmingly negative, largely due to the simplistic and fragmented conceptualisations assumed in prior work. The purpose of the current paper is to present a comprehensive review of the umbrella term of compensatory consumption, incorporating a continuum of behaviours and accounting for the pre-and post-consumption periods including both po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 156 publications
(245 reference statements)
3
62
0
2
Order By: Relevance
“…Obtaining caloric resources in times of scarcity may reflect an adaptive motivation to compensate for (future) scarcity of resources (see also Laran & Salerno, ; Swaffield & Roberts, ). Overall, the present research may provide additional support for the notion that food consumption in response to scarcity is not domain restricted but may also be evoked by non‐food resources (Briers & Laporte, ; Koles, Wells, & Tadajewski, ). Especially when people with low income live in neighbourhoods in which they are more frequently exposed to unhealthy (often tempting) foods (Cummins, ; Darmon & Drewnowski, ), adopting a healthy diet may be a difficult endeavour when also experiencing scarcity.…”
Section: Introductionsupporting
confidence: 71%
“…Obtaining caloric resources in times of scarcity may reflect an adaptive motivation to compensate for (future) scarcity of resources (see also Laran & Salerno, ; Swaffield & Roberts, ). Overall, the present research may provide additional support for the notion that food consumption in response to scarcity is not domain restricted but may also be evoked by non‐food resources (Briers & Laporte, ; Koles, Wells, & Tadajewski, ). Especially when people with low income live in neighbourhoods in which they are more frequently exposed to unhealthy (often tempting) foods (Cummins, ; Darmon & Drewnowski, ), adopting a healthy diet may be a difficult endeavour when also experiencing scarcity.…”
Section: Introductionsupporting
confidence: 71%
“…To summarise, panic buying can be viewed as a compensatory consumption behaviour, which suggests that individuals turn to purchasing products as a way to restore deficits triggered by perceived needs and desires that can only be fulfilled indirectly [37]. In this regard, the deficit refers to the loss of control over the situation, and this can be compensated through problem solving such as panic buying.…”
Section: Coping Behaviourmentioning
confidence: 99%
“…People’s increased boredom from limited activities and sensation-seeking expressions during the pandemic gave us good reason to speculate that people’s willingness to consume and impulsive buying tendencies may climb significantly after the pandemic is effectively controlled. By satisfying an individual’s needs through payment, consumption is an effective means to elevate arousal levels ( Batra and Ghoshal, 2017 ; Koles et al, 2018 ). Yan et al (2016) demonstrated that individuals’ willingness to consume would greatly increase if they try to seek external stimuli to enhance their arousal.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%